Peritoneal Protein Loss, Inflammation, and Nutrition: Refuting Myths - Malho Guedes, Anabela; Calças Marques, Roberto; Ribeiro, Brigitte; Fernandes, Mónica T.; Faísca, Marília; Silva, Ana Paula; Bragança, José; Rodrigues, Anabela (Frontiers in Medicine, 2022)
Peritoneal protein loss (PPL) has been correlated with mortality, malnutrition and inflammation. More recently overhydration was brought to the equation. This study aims to review classic and recent factors associated with PPL. Prevalent and incident peritoneal dialysis (PD) patients were included. Dialysate and serum IL-6 was obtained during PET. Hydration and nutritional status were assessed by bio-impedance. Linear regression and Cox regression were performed. The 78 included patients presented median values of PPL 4.8 g/24h, serum IL-6: 5.1 pg/mL, and IL-6 appearance rate 153.5 pg/min. Mean extracellular water excess (EWexc) was 0.88 ± 0.94L, and lean body mass index (LBMI) 17.3 ± 2.4 kg/m2. After mean follow-up of 33.9 ± 29.3 months, twelve patients died. Linear univariable analysis showed positive associations between PPL and small solute transport, body composition (LBMI and EWexc), comorbidities and performing CAPD (vs cycler). PPL correlated positively with dialysate appearance rate of IL-6, but not with serum IL-6. Linear multivariable analysis confirmed positive association between PPL and EWexc (p=0.012; 95%CI:4.162-31.854), LBMI (p=0.008; 95%CI:1.720-11.219) and performing CAPD (p=0.023; 95%CI:4.375-54.190). In survival analysis, no relationship was found between mortality and PPL. Multivariable Cox regression showed Charlson Comorbidity Index (HR: 1.896, 95%CI:1.235-2.913), overhydration (HR: 10.034, 95%CI:1.426-70.587) and lower PPL (HR: 0.576, 95%CI:0.339-0.978) were predictors for mortality. Overhydration, was a strong predictor of PPL, overpowering variables previously reported as determinants of PPL, namely clinical correlates of endothelial dysfunction or local inflammation. PPL were not associated with malnutrition or higher mortality, emphasizing the importance of volume overload control in PD patients.